Penerapan Basis Data Pada Perusahaan e-commerce - Mei Anriani Ritonga; Cut Fadilah; Gusti Erli Anggi Lubis; Fadli Yusuf; Nurbaiti Nurbaiti (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This study aims to examine the benefits of implementing databases in e-commerce companies in various companies, not only in one type of company, but in various companies such as furniture, shoe stores, underwear flower shops, garment industry and women's clothing sales companies so that we know the benefits of databases. not only in one company but in general. The sample of this research is previous articles that have reviewed the benefits of databases in e-commerce companies. In this study, the sample used was 5 articles that discussed the benefits of databases. The results showed the benefits of implementing database company data, including accelerating and facilitating knowledge of product sales data, producing company transaction reports on goods quickly and efficiently, providing convenience and comfort for customers to place orders or returning purchases of goods without having to go to the point of sale, Simplify the management of product data ordering data thereby reducing costs very large operations, provide more accurate data, and increase consumer knowledge because of the web about features that can be selected to view product descriptions, sizes and promotions.